Change in diffusion weighted imaging after induction chemotherapy outperforms RECIST guideline for long-term outcome prediction in advanced nasopharyngeal carcinoma - Qi Yong H. Ai; Ho Sang Leung; Frankie K.F. Mo; Kaijing Mao; Lun M. Wong; Yannis Yan Liang; Edwin P. Hui; Brigette B.Y. Ma; Ann D. King (Cancer Imaging)
Abstract Purpose To investigate change in diffusion weighted imaging (DWI) between pre-treatment (pre-) and after induction chemotherapy (post-IC) for long-term outcome prediction in advanced nasopharyngeal carcinoma (adNPC). Materials and methods Mean apparent diffusion coefficients (ADCs) of two DWIs (ADCpre and ADCpost−IC) and changes in ADC between two scans (ΔADC%) were calculated from 64 eligible patients with adNPC and correlated with disease free survival (DFS), locoregional recurrence free survival (LRRFS), distant metastases free survival (DMFS), and overall survival (OS) using Cox regression analysis. C-indexes of the independent parameters for outcome were compared with that of RECIST response groups. Survival rates between two patient groups were evaluated and compared. Results Univariable analysis showed that high ΔADC% predicted good DFS, LRRFS, and DMFS p < 0.05), but did not predict OS (p = 0.40). Neither ADCpre nor ADCpost−IC (p = 0.07 to 0.97) predicted outcome. Multivariate analysis showed that ΔADC% independently predicted DFS, LRRFS, and DMFS (p < 0.01 to 0.03). Compared with the RECIST groups, the ΔADC% groups (threshold of 34.2%) showed a higher c-index for 3-year (0.47 vs. 0.71, p < 0.01) and 5-year DFS (0.51 vs. 0.72, p < 0.01). Compared with patients with ΔADC%<34.2%, patients with ΔADC%≥34.2% had higher 3-year DFS, LRRFS and DMFS of 100%, 100% and 100%, respectively (p < 0.05). Conclusion Results suggest that ΔADC% was an independent predictor for long-term outcome and was superior to RECIST guideline for outcome prediction in adNPC. A ΔADC% threshold of ≥ 34.2% may be valuable for selecting patients who respond to treatment for de-escalation of treatment or post-treatment surveillance.